The soliton interaction in weakly nonlocal nonlinear media on the external potentials - Mohd Busul Aklan, Nor Amirah; Umarov, Bakhram A. (IOP Publishing, 2017)
This paperwork had observed the analytical and numerical study of the solitons interaction and scattering of the weakly nonlocal nonlinear media on the external potential called delta potential. Using generalized form of Nonlinear Schrodinger Equation (NLSE) which is Cubic-Quintic NLSE, in weakly nonlocal nonlinear media, we applied the variational approximation method to derive the equations for soliton parameters evolution during scattering process. Then a direct numerical simulation of NLSE is used to check the validity of approximations, considering the soliton initially located far from potential. Depending on initial velocity of the soliton, the phenomenon of reflection and transmission of the soliton through the potential have been showed. The critical values of the velocity separating these two scenarios have been identified.